2012
DOI: 10.1016/j.jnc.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Troublesome neighbours: Changing attitudes towards chimpanzees (Pan troglodytes) in a human-dominated landscape in Uganda

Abstract: a b s t r a c tLong-term human-wildlife sympatry depends on the willingness and capacity of local people to coexist with wild animals. With human population growth and deforestation for agriculture, farmers increasingly live in proximity to wildlife, including large mammals of conservation concern. Understanding local perspectives and concerns regarding wildlife is essential for informing appropriate management strategies that reduce conflicts and promote sustainable coexistence. Social science approaches ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 41 publications
1
68
0
Order By: Relevance
“…However, it is also possible that farmers were potentially more likely to report chimpanzee foraging on a valuable staple crop such as cassava than domestic fruits because these are in most villages typically grown around individual households and harvested mainly for self-consumption. A similar situation was described by McLennan and Hill (2012) in Uganda where farmers tolerated consumption of fruits by chimpanzees like guavas but not cash crops like sugarcane, cocoa or bananas. Still, farmers in our study reported domestic fruits as being targeted especially by chimpanzees and monkeys.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, it is also possible that farmers were potentially more likely to report chimpanzee foraging on a valuable staple crop such as cassava than domestic fruits because these are in most villages typically grown around individual households and harvested mainly for self-consumption. A similar situation was described by McLennan and Hill (2012) in Uganda where farmers tolerated consumption of fruits by chimpanzees like guavas but not cash crops like sugarcane, cocoa or bananas. Still, farmers in our study reported domestic fruits as being targeted especially by chimpanzees and monkeys.…”
Section: Discussionsupporting
confidence: 61%
“…There was indeed a gradient with chimpanzees being ranked higher (LA and MO) where farmers mentioned growing more seasonal crops and fewer cash crops and also reporting selling fewer surpluses, indicating a higher dependency of seasonal cultivation for subsistence. The degree to which farmers viewed chimpanzees as a threat to their agricultural yield may also be related to the extent of overlap between the chimpanzees' home range and farmlands in the landscape, the contribution of different crop species to chimpanzees' diet locally (McLennan & Hill, 2012) or whether farmers have direct experience of chimpanzee crop foraging (although there was no reported variation across sites in this study), and their level of tolerance of chimpanzee offtake (although chimpanzees were reportedly less likely to threaten people at LA which would indicate that perhaps farmers are more tolerant of chimpanzee crop-foraging at this site) (Webber & Hill, 2014). These alternative explanations warrant further investigation to reveal patterns of similarity or differences across sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, some respondents were afraid of chimpanzees and were reluctant to adopt crop protection strategies due to their possible aggressive behaviour, as has been seen elsewhere [49]. This is a potential concern for conservation locally because people are likely to become intolerant of a situation they cannot control.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to financial benefits, beekeeping holds the potential for implementing bee hive fences (King et al 2009), and has been proven to be highly successful in Kenya (King et al 2011). However, in areas where chimpanzees (P. troglodytes) occur honey production might not be feasible as the primates can raid and destroy these beehives (McLennan & Hill 2012;Sanz & Morgan 2009). Trials should test the effectiveness and feasibility of such fences for susceptible farms around the BCA.…”
Section: Discussionmentioning
confidence: 99%